On the Strategy for Development of Western Regions of PRC (Journal of Oriental Studies, 2018)
In the first part of the article, the socio-political reasons for the implementation the developmentstrategy of the Western regions of the PRC, the time and stages of implementing the strategy are determined.The projects of the PRC government on development of the Western regions, financial issuesand general provisions of the project implementation are considered. In the second part of the article,the development policy of Xinjiang is considered as part of the development strategy of the Westernregions, legislative acts, plans, amounts of funding, the goals pursued and the results of development todate. The article notes that the decrease in the water volume of Transboundary Rivers is unprofitable forKazakhstan, nevertheless, that the development of the Western regions of the PRC, especially the socialand economic development of Xinjiang, is very beneficial for Kazakhstan.In the first part of the article, the socio-political reasons for the implementation the developmentstrategy of the Western regions of the PRC, the time and stages of implementing the strategy are determined.The projects of the PRC government on development of the Western regions, financial issuesand general provisions of the project implementation are considered. In the second part of the article,the development policy of Xinjiang is considered as part of the development strategy of the Westernregions, legislative acts, plans, amounts of funding, the goals pursued and the results of development todate. The article notes that the decrease in the water volume of Transboundary Rivers is unprofitable forKazakhstan, nevertheless, that the development of the Western regions of the PRC, especially the socialand economic development of Xinjiang, is very beneficial for Kazakhstan.